What is an "Emotion" in the Hebrew Bible? - Mirguet, Françoise (Biblical Interpretation, 2016)
As emotions and feelings in the Hebrew Bible are starting to receive scholarly attention, I question here the appropriateness of applying the modem concept of "emotions" to Biblical Hebrew. To which extent do our "emotions" fit the way Biblical Hebrew organizes human experience? The first part of the article analyzes a few Hebrew words commonly translated by terms of emotion in modem languages. Based on existing scholarship and a brief study of the words in their literary contexts, I suggest that the terms are not limited to the expression of what we call emotions; rather, they also include actions, movements, ritual gestures, and physical sensations, w ithout strict dissociation among these different dimensions. This observation casts doubt on the existence of an isolated emotional realm in Biblical Hebrew's organization of human experience. In the second half, I proceed in an opposite way: I start from a given situation - scenes where the self faces the suffering affecting another person and initiates different actions in favor of the sufferer. The examples highlight that the experience we commonly shape as an "emotion" - compassion or sympathy - does not receive such a construction in Biblical Hebrew. Besides, the experience affects the self not so much in its individuality as in its social relationships; as such, it also functions inside a given social hierarchy. I conclude by considering the potential impact that this reframed view on biblical "emotions" may have on this nascent field.